2011
DOI: 10.3892/mmr.2011.512
|View full text |Cite
|
Sign up to set email alerts
|

‘Genetic profiling’ and ovarian cancer therapy (Review)

Abstract: Abstract. High variability observed among ovarian cancer patients in response to the same therapy and the related toxicity may be correlated to gene polymorphisms and genetic alterations affecting the metabolism of drugs commonly used to treat this tumor. Recent studies have shown a correlation between the polymorphisms characterizing GSTM1-T1 detoxifying enzymes and poor outcome in advanced ovarian cancer patients treated with platinum/paclitaxel-based chemotherapy. Multidrug resistance 1 (mdr-1) polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Alterations in DNA methylation have been hypothesized to play a role, because DNA methylation is one mechanism cells employ to respond to environmental stimuli [29]. Platinum-based chemotherapy is the primary line of drug therapy for all advanced stage EOC cases; carboplatin combined with paclitaxel is the standard of care, irrespective of histotype [86,87]. Early studies on breast and ovarian cancer cell lines reported sensitivity to platinum-based chemotherapy in cells with either mutant or hypermethylated BRCA1 [8890].…”
Section: Clinical Aspects Of Epigenetics In Eocmentioning
confidence: 99%
“…Alterations in DNA methylation have been hypothesized to play a role, because DNA methylation is one mechanism cells employ to respond to environmental stimuli [29]. Platinum-based chemotherapy is the primary line of drug therapy for all advanced stage EOC cases; carboplatin combined with paclitaxel is the standard of care, irrespective of histotype [86,87]. Early studies on breast and ovarian cancer cell lines reported sensitivity to platinum-based chemotherapy in cells with either mutant or hypermethylated BRCA1 [8890].…”
Section: Clinical Aspects Of Epigenetics In Eocmentioning
confidence: 99%
“…In the past, commonly used drugs included cyclophosphamide, melphalan and chlorambucil (16). When cisplatin was introduced to clinical practice in 1978, platinum-based therapy was shown to generate a higher number of responsive patients, increase response duration and progression-free interval (16). Since then, platinum derivatives, such as cisplatin and carboplatin, have become the standard of care for ovarian cancer patients.…”
Section: Therapeutic Regimens For Eocmentioning
confidence: 99%
“…Platinum (carboplatin) combined with a taxane (paclitaxel) is the primary therapeutic regimen in EOC, regardless of histological type [71,72]. Carboplatin is incorporated into DNA, inducing formation of adducts and eliciting mismatch repair which, in turn, activates apoptosis [73].…”
Section: Dna Methylation and Chemotherapy Resistance In Ovarian Camentioning
confidence: 99%